(untitled) (Journal of Oriental Studies, 2025)
The article deals with the content and methodological features of teaching the history of the Republic of Turkey at Yerevan State University. The structure of the course is analyzed within the framework of the "Turkology" and "Azerbaijani Studies" educational programs of the YSU Faculty of Oriental Studies, where the course "History of the Republic of Turkey" is the logical continuation of the courses "History of the Seljuk and Early Ottoman Periods" and "History of the Ottoman Empire." The teaching process combines traditional methods - lectures, seminars, testing assignments - with modern, student-centered approaches - debate, simulation-based learning, demonstration methods, as well as the use of visual and cartographic materials. Combination of these methods contributes to the formation of students’ critical thinking, analytical skills, and research capabilities. An important component of the educational process’s effectiveness is also the availability of an Armenian-language academic textbook, which ensures the scientific validity and in-depth understanding of the material being taught.